Toy Projects Considered Harmful. (Communications of the ACM, 2006)
The article discusses methodology for teachers of computer science students. Toy projects, which are programming challenges that students must complete, are often used as training and teaching exercises but can actually prove harmful if they are not contextually related to real-world applications of computer programming. In order to prepare students for the real-world, teachers must make sure to create a context in which student programming matters beyond the academic setting, and ensure students are motivated to program for more than their grades.